2024
DOI: 10.1590/1519-6984.256944
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antioxidant activity of Panax ginseng and Hedysarum neglectum root crop extracts

Abstract: In order to ensure the timely and uninterrupted supply of medicinal plant raw materials, the methods of cultivation of plant cell cultures, namely, the production of plant root cultures, are relevant. In this paper, the geroprotective potential of Hedysarum neglectum Ledeb and Panax ginseng C. A. Mey root cultures is studied. They were cultured under in vitro conditions by transforming the rhizome (H. neglectum) and seed seedlings (P. ginseng) with Agrobacterium rhizogenes 15834 Swiss. To identify the geroprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Biologically active substances are known for a great variety of therapeutic effects with maximal activity and minimal side effects [ 25 ]. Their antioxidant properties are used against cancer, memory impairment, neurodegenerative diseases, atherosclerosis, diabetes, and cardiovascular diseases [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biologically active substances are known for a great variety of therapeutic effects with maximal activity and minimal side effects [ 25 ]. Their antioxidant properties are used against cancer, memory impairment, neurodegenerative diseases, atherosclerosis, diabetes, and cardiovascular diseases [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analytical mass spectrometry is a complex term, referring to three major research tasks of qualitative , quantitative , and structural analyses . However, pursuing the exact chemometrics (|r| = 1) is a challenging analytical task [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. Among theoretical model equations that are particularly relevant are those producing exact method performance.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have suggested that the use of antioxidant compounds is an important strategy for retaining cellular youth (Dyshlyuk et al, 2024;Silva et al, 2021), which can be linked to the enhancement of hair fiber. Other papers have also highlighted the utilization of antioxidant compounds is a crucial strategy for preserving cellular young.…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%